Exploring biosurfactant from Halobacterium jilantaiense as drug against HIV and zika virus: fabrication, characterization, cytosafety property, molecular docking, and molecular dynamics simulation - Almuhayawi, Mohammed S.; Elshafey, Naglaa; Hagagy, Nashwa; Selim, Samy; Al Jaouni, Soad K.; Sofy, Ahmed R.; Samy, Mennatalla; Gattan, Hattan S.; Alruhaili, Mohammed H.; Alharbi, Mohanned Talal; Nagshabandi, Mohammed K.; Tarabulsi, Muyassar K.; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Biosurfactants are surface-active molecules with unique qualities and various uses.Many microorganisms produce secondary metabolites with surface-active characteristics that serve various antiviral functions. The HIV and Zika viruses were chosen for this study because they can spread from mother to child and result in potentially fatal infections in infants.Halophilic bacteria from the Red Sea solar saltern in Egypt were screened using drop collapse, emulsification activity, and oil displacement assays to produce biosurfactants and bioemulsifiersemulsifiers. Halobacterium jilantaiense strain JBS1 was the most effective strain of the Halobacteriaceae family. It had the best oil displacement test and emulsification activity against kerosene and crude oil, respectively. Among the ten isolates, it produced the most promising amount of biosurfactant, also recognized by the GC-MASS library. In this study, biosurfactants from halophilic bacteria were evaluated This study evaluated biosurfactants from halophilic bacteria as potential antiviral drugs. Some of the computer methods we use are molecular docking, ADMET, and molecular dynamics. We use model organisms like the HIV reverse transcriptase (PDB: 5VZ6) and the Zika virus RNA-dependent RNA polymerase (ZV-RdRP). Molecular docking and molecular dynamics are used to make the best complexes with 5VZ6 HIV-RT and flavone (C25) and 5wz3 ZV-RdRP and ethyl cholate (C8). Testing for ADMET toxicity on the complex revealed that it is the safest medicine conceivable. The 5VZ6-C25 and 5wz3-C8 complexes also followed the Lipinski rule. They made five hydrogen bond donors and ten hydrogen bond acceptors with a 500 Daltons MW and a 5:1 octanol/water partition coefficient. Finally, extreme settings require special particular adaptations for stability, and extremophile biosurfactants may be more stable in these situations.